The Effect of Problem-Based Learning on the First-Grade Students' Reading Comprehension at SMK GKPI 2 Pematangsiantar - Kris Jhon Fidelis Simbolon; Bernieke Anggita Ristia Damanik; Dumaris E. Silalahi (International journal of technology and education research, 2026)
This research discusses the effect of Problem-Based Learning (PBL) on students’ reading comprehension at SMK GKPI 2 Pematangsiantar. This research used a quantitative method with a quasi-experimental design. The population of this research consisted of the first-grade students of SMK GKPI 2 Pematangsiantar in the academic year 2025/2026. The sample consisted of 31 students divided into two groups: 16 students in the experimental class and 15 students in the control class. The experimental class was taught using Problem-Based Learning, while the control class was taught using the conventional teaching method. The instrument used in this research was a reading comprehension test consisting of multiple-choice and short-answer questions. The data were collected through pre-test and post-test. The results showed that the students in the experimental class experienced greater improvement in reading comprehension compared to the control class. The statistical analysis using the Mann–Whitney U Test indicated that there was a significant difference between the post-test scores of the experimental and control groups. Therefore, the alternative hypothesis (H₁) was accepted and the null hypothesis (H₀) was rejected. Based on the findings, it can be concluded that Problem-Based Learning has a significant effect on students’ reading comprehension.